Anomalous Pore‐Density Dependence in Nanofluidic Osmotic Power Generation. Issue 5 (25th March 2018) - Su, Jianjian; Ji, Danyan; Tang, Jialiang; Li, Hao; Feng, Yaping; Cao, Liuxuan; Jiang, Lei; Guo, Wei
Abstract : Over‐crowded nanopore arrangement impairs charge selectivity and induces strong ion concentration polarization (ICP) that undermines the osmotic energy conversion, showing anomalous pore‐density dependence. Abstract: Osmotic power generation in biomimetic nanofluidic systems has attracted considerable research interest owing to the enhanced performance and long‐term stability. Towards practical applications, when extrapolating the materials from single‐nanopore to multi‐pore membranes, conventional viewpoint suggests that, to gain high electric power density, the porosity should be as high as possible. However, recent experimental observations show that the commonly‐used linear amplification method largely overestimates the actual performance, particularly at high pore density. Herein, we provide a theoretical investigation to understand the reason. We find a counterintuitive pore‐density dependence in high porosity nanofluidic systems that, once the pore density approaches more than 1×10 9 pores/cm 2, the overall output electric power goes down with the increasing pore density. The excessively high pore density impairs the charge selectivity and induces strong ion concentration polarization, which undermines the osmotic power generation process. By optimizing the geometric size of the nanopores, the performance degradation can be effectively relieved. These findings clarify the origin of the unsatisfactory performance of the current osmotic nanofluidic power sources, and provide insights to further optimize the device.